KAJIAN BIBLIKA TENTANG YESUS SEBAGAI PINTU DAN GEMBALA MENURUT YOHANES 10:1-18 - jonar Situmorang (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2019)
This paper examines two things, which is Jesus' statement about Himself in the Gospel of John and a statement that begins with: "I ..." (Greek: εγω ειμι = ego eimi). These two statements come out of the phrase "I am the door" and "I am the good shepherd." Theologically, especially in Christology, this emphasizes His personality as God, who can be an example of leadership in the church. The purpose is to describe Jesus' declaration that He is the door and the Good Shepherd in John 10: 1-18 and its implications for the ministers as church leaders. The methodology in this research is descriptive analysis. As a result, the two statements of Jesus in John 10: 1-18 reflect the example of Jesus as the Good Shepherd.